Legal consequences of the absence of state registration of agreements with the patent office of the Republic of Belarus - Lando, Darya D. (Journal of the Belarusian State University. Law, 2024)
The article justifies the importance of naming sublicense agreements, subfranchise agreements in the norms of civil legislation of the Republic of Belarus, in particular, in order to reflect reliable information about the state registration of such agreements. The issue of legal consequences of failure to register certain agreements on transfer and granting of rights to industrial property is considered, the remaining gaps in legal regulation are identified. In the light of amendments to the Civil Code of the Republic of Belarus from 19 November 2024 it is proposed do not recognise franchise and subfranchise agreements invalid due to the lack of their state registration with the patent office regardless of the composition of the license complex provided.